Students' Writing Ability In Recount Text At The Tenth Grade Of SMKS Perbankan Yaris Duri - Dwi Royani, Indri; Deswarni, Dini (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2023)
The purpose of this study was to determine the student’s writing ability in recount text at the tenth grade of SMKS Perbankan Yaris Duri. This research is a used quantitative approach and is also designed using descriptive methods. The population in this research is the tenth grade of SMKS Perbankan Yaris is which consists of 20 students’ in the academic year of 2020/2021. In this research, the test is to write students’ experience on holiday to measure students’ writing skills in recount text. There is a topic provided the students developed it into a short recount text composition. The writer held one phase of the test in one day. This phase is a test for validating the instrument of the research. The result of the analysis showed that out of 20 samples there were 5 samples with a category score as Good (B) or with a percentage of 25% and 15 samples category as Excellent (A) or with a percentage of 75%. From the result of the research that the writer did, answer the question of the formulation of the problem “How is student’s writing ability in recount text at the tenth grade of SMKS Perbankan Yaris Duri academic year 2020/2021? It could be concluded, that the student’s writing ability in recount text at the tenth grade of SMKS Perbankan Yaris Duri showed excellent result